New features in Office 2007 - Miles, Timothy J.; Conway, Pamela; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course covers those features of Microsoft Office 2007 that are new to the Office system, with dedicated units for the new features of each application. In Word, you will learn to use Quick Parts and themes, review changes in paragraph styles, and see changes in inserting tables and formatting objects. In Excel you will learn to use changes in PivotTables and data tables, apply new conditional formatting and review enhancements in charting. In PowerPoint you will understand the changes in slide layouts and slide masters, how to use and modify design themes, apply new effects to graphics and work with SmartArt. In Outlook you will review changes in tasks, learn to use search folders, add RSS feeds, and see changes in sharing calendars. In Access, you will learn how to use new templates, create a new table, understand changes in sorting and filtering and work with new features in forms and reporting. In addition, you will learn how to navigate in the new user interface by working with the Ribbon and Quick Access Toolbar. You will also learn the benefits and features of the new XML file format. Includes everything needed to work effectively within the new suite of applications."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 9, 2013).
Presenter, Timothy Miles, Pamela Conway.
Keywords: Microsoft Office; Business -- Computer programs; Office management -- Computer programs; Electronic books